Transmission network expansion planning under a Tabu Search approach. - Da Silva, E.L (IEEE Transactions on power systems)
This paper describes an implementation of Tabu Search to cope with long-term transmission network expansion planning problems. Tabu Search is a metaheuristic proposed in 1989 to be applied to combinatorial problems. To assess the potential of our approach we test it with two cases of transmission network expansion planning. The results obtained by our approach let us to conclude that TS is a robust and promising technique to be applied in this problem